Novel respiratory syncytial virus (RSV) genotype ON1 predominates in Germany during winter season 2012-13 - Tabatabai, Julia; Prifert, Christiane; Pfeil, Johannes; Grulich-Henn, Jürgen; Schnitzler, Paul (PLOS ONE, 2014)
Respiratory syncytial virus (RSV) is the leading cause of hospitalization especially in young children with respiratory tract infections (RTI). Patterns of circulating RSV genotypes can provide a better understanding of the molecular epidemiology of RSV infection. We retrospectively analyzed the genetic diversity of RSV infection in hospitalized children with acute RTI admitted to University Hospital Heidelberg/Germany between October 2012 and April 2013. Nasopharyngeal aspirates (NPA) were routinely obtained in 240 children younger than 2 years of age who presented with clinical symptoms of upper or lower RTI. We analyzed NPAs via PCR and sequence analysis of the second variable region of the RSV G gene coding for the attachment glycoprotein. We obtained medical records reviewing routine clinical data. RSV was detected in 134/240 children. In RSV-positive patients the most common diagnosis was bronchitis/bronchiolitis (75.4%). The mean duration of hospitalization was longer in RSV-positive compared to RSV-negative patients (3.5 vs. 5.1 days; p<0.01). RSV-A was detected in 82.1%, RSV-B in 17.9% of all samples. Phylogenetic analysis of 112 isolates revealed that the majority of RSV-A strains (65%) belonged to the novel ON1 genotype containing a 72-nucleotide duplication. However, genotype ON1 was not associated with a more severe course of illness when taking basic clinical/laboratory parameters into account. Molecular characterization of RSV confirms the co-circulation of multiple genotypes of subtype RSV-A and RSV-B. The duplication in the G gene of genotype ON1 might have an effect on the rapid spread of this emerging RSV strain.